LPS Regulates Endometrial Immune Homeostasis and Receptivity Through the TLR4/ERK Pathway in Sheep - Jinzi Wei; Xing Fan; Xiaorui Zang; Yu Guo; Wenjie Jiang; Meiyu Qi; Hongbing Han; Yuchang Yao (Animals, 2025)
In sheep production, due to the limitations of breeding conditions, the uteri of ewes are often infected with bacteria, resulting in the failure of embryo implantation or loss, causing huge losses to the sheep industry. Therefore, in this study, by using RT-qPCR, Western blot, and immunofluorescence, we investigated the effects of LPS infusion on the immune microenvironment and endometrial receptivity, which play an important role in the process of embryo implantation in ruminants, during the three critical periods of embryo implantation in sheep. The results showed that LPS infusion at day 12, day 16, and day 20 significantly increased the expression of Th1 cytokines (TNF-α, IL-1β, IL-8, IL-6), while significantly decreasing the expression of Th2 cytokines (IL-4 and IL-10) and disrupting the expression of implantation factors, such as ITGB3, ITGB5, VEGF, and LIF, in the endometrial tissues of sheep. Additionally, the protein expression level of TLR4 and the phosphorylation level of ERK were significantly elevated at day 12, day 16, and day 20 after LPS infusion, suggesting that LPS may impair endometrial receptivity through the TLR4/ERK pathway. Validation was conducted in a receptive model of sEECs using TLR4 and ERK phosphorylation inhibitors. Compared with the LPS group, TLR4 and ERK phosphorylation inhibitors significantly reduced the expression of TLR4 and p-ERK, down-regulated Th1 cytokines, up-regulated Th2 cytokines, and alleviated the disruption of genes for attachment. Treatment with 50 μM PTE can significantly alleviate the abnormal expression of implantation genes caused by LPS, and its mechanism may be related to the regulation of the ERK signaling pathway.